Ocupações infantis e pandemia da COVID-19: a percepção das mães - Betti, Ana Claudia Moron (Universidade Federal de São Carlos, 2021)
Occupations, the object of study and practice in Occupational Therapy, are understood as human, daily activities, which people perform individually, in family or in the community, with purposes and meanings. Children, as they perform occupations, learn, master and put into practice new skills, develop autonomy and independence and feelings of belonging and self-esteem. With the emergence of the COVID-19 pandemic, the adoption of distance measures and adjustments in the formats of school and work activities were taken in a worldwide proportion, as a way to reduce the spread of the virus. Questioning the influences of social distance in children's occupations and the challenges and coping strategies encountered by families, this study aimed to analyze, from the perspective of guardians, the influence of social distance on the participation of children from 4 to 6 years old in their occupations and routines, during the COVID-19 pandemic, as well as identifying the resources available and used by families to support and promote participation in this context. Data collection took place through an online questionnaire answered by the adults responsible for the child. 330 responses were obtained, from which statistical analysis (closed questions) and thematic analysis (open questions) were carried out. The research reached a not very heterogeneous group of participants, recognized as a limitation of the study, however, stimulating discussions about the routines and occupations of children and families. It was identified that, although the routine changes may have restricted the opportunities for occupations, the routines were structuring for the participation in the occupations. Regarding families, influenced by the socioeconomic and cultural contexts and central to the construction and support of these routines, the mothers' overload with domestic tasks, work and care for their children stood out; the mental health of adults and children and the strengthening of family bonds. Opportunities were identified to monitor the global development of their children, in addition to gains in autonomy, independence and participation in domestic tasks. About school occupation and the role of students, we discussed the changes in the performance of this occupation, the harmful influences caused by the reduction of social contact with people at school, the challenges of adults in accumulating tasks and following classes, but also about possibilities to monitor and participate in children's school development. Regarding the support and information networks found by the families, the role of the teacher was highlighted as the main source of information identified by the families and about the families themselves as the main source of emotional support. It is hoped that, as students of the occupations, we can recognize and value the routines and natural contexts and encourage children and their families to find meaning and purpose in their occupations, intervening in a joint construction, not as a standardized orientation to be followed. It is suggested that future studies seek greater heterogeneity related to the age group of the participants, socioeconomic characteristics, education, focus on gender discussions including maternal overload and listening to the children's perception as protagonists of this process.
Child occupations and pandemic of COVID-19: mother's perception
Keywords: Desenvolvimento ocupacional; Ocupações infantis; Infância; Pandemia COVID-19; Distanciamento social; Occupational development; Child occupations; Childhood; COVID-19 pandemic; Social distancing; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL